2015
DOI: 10.1080/19476337.2015.1007532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of extracts of banana inflorescences (Musa cavendishii)

Abstract: This study evaluated the content of phenolic compounds and flavonoids and the antioxidant potential of the banana inflorescence extract from the species Musa cavendishii as well as investigated the effects of extraction conditions (conventional and ultrasound) on obtaining these compounds. The extracts showed high contents of phenolics and flavonoids and potential as an antioxidant agent. The best results were found under the following extraction conditions: temperature 60°C, ethanol concentration 50%, time 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…This was probably due to the antioxidant capacity of the banana inflorescence, which has been reported by Schmidt et al (2015), Roobha et al (2011), and Padam et al (2012). Lee et al (2005) also reported a delay in the lipid oxidation of burgers with added plant extract; burgers with 500 ppm of rosemary extract had lipid oxidation lower than the control burgers (without antioxidant) and oxidation equivalent to burgers with 200 ppm of butylated hydroxyanisole (BHA).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This was probably due to the antioxidant capacity of the banana inflorescence, which has been reported by Schmidt et al (2015), Roobha et al (2011), and Padam et al (2012). Lee et al (2005) also reported a delay in the lipid oxidation of burgers with added plant extract; burgers with 500 ppm of rosemary extract had lipid oxidation lower than the control burgers (without antioxidant) and oxidation equivalent to burgers with 200 ppm of butylated hydroxyanisole (BHA).…”
Section: Discussionmentioning
confidence: 86%
“…Some studies have shown that banana inflorescence has high antioxidant potential (Padam, Tin, Chye, & Abdullah, 2012;Roobha, Saravanakumar, Aravinthan, & Devi, 2011;Schmidt, Prestes, Kubota, Scapin, & Mazutti, 2015) and it may represent a viable and economical source of bioactive compounds that are beneficial to health.application of the extract of banana inflorescence as a natural antioxidant in meat products.…”
Section: Introductionmentioning
confidence: 99%
“…However, mango had shown a decrease in flavonoid content from unripe stage to ripen stage but significantly increased from ripen stage to overripen stage (Figure 6). The flavonoid is a natural pigment that can naturally be found in plant in which it can be affected by the fruit peel colouration (Schmidt et al, 2015). The best stage to consume fruit is when the fruit is immature to get high flavonoid intake.…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 99%
“…32 Nevertheless, the antioxidant activity of crude extracts from F. altissima leaves was better than those of several extracts in the previous studies. 40,41 3.3.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%